Synthesis and Antimicrobial Activity of Some Thiadiazolo Thienopyrimidines - SRIVASTAVA, SAJAL; DAS, BARNALI; RAGHUPRASAD, M.; MOHAN, S. (Asian Journal of Chemistry, 2010)
A series of compounds RP-2 to RP-9 were synthesized from 2-chloromethyl-1,3,4-thiadiazolo(2,3-b)6,7,8,9-tetrahydro-benzo(b)thieno(3,2-e)pyrimidin-5(4H)-one by refluxing with various substituted aromatic amine in dioxan using triethylamine as a catalyst. The IR and NMR spectra of the compounds were were investigated. All the compounds were screened for antibacterial activity against one grampositive and one gram-negative bacteria.